Consciousness : a very short introduction - Blackmore, Susan (Oxford University Press, 2005)
Consciousness, 'the last great mystery for science', has now become a hot topic. How can a physical brain create our experience of the world? What creates our identity? Do we really have free will? Could consciousness itself be an illusion?